2020
DOI: 10.1111/bjd.19551
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical ropivacaine in children and young adults with hereditary epidermolysis bullosa

Abstract: Mrowietz U, Kragballe K, Reich K et al. Definition of treatment goals for moderate to severe psoriasis: a European consensus. Arch Dermatol Res 2011; 303:1-10. 2 Wan MT, Alvarez J, Shin DB et al. Head-to-head trials of systemic psoriasis therapies: a systematic review of study design and maximum acceptable treatment differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…• A recent study based on topical applications of a nondiluted injection formula of ropivacaine 0.2% on EB wounds during dressing changes showed that topical ropivacaine could reduce pain. 44 Nevertheless, there are some limitations of this pilot study due to the small number of patients and the short follow-up period. Particularly, long-term safety, tolerance and pharmacokinetics studies need to be performed before proposing routine clinical use.…”
Section: Agementioning
confidence: 94%
“…• A recent study based on topical applications of a nondiluted injection formula of ropivacaine 0.2% on EB wounds during dressing changes showed that topical ropivacaine could reduce pain. 44 Nevertheless, there are some limitations of this pilot study due to the small number of patients and the short follow-up period. Particularly, long-term safety, tolerance and pharmacokinetics studies need to be performed before proposing routine clinical use.…”
Section: Agementioning
confidence: 94%
“…Several agents are in early phase trials but recommendations for best clinical practice are few. To reduce dressing change pain, application of 0.2% topical ropivacaine (anesthetic) 15 minutes before soaking the dressings was shown to reduce around 3 points of pain scale in 8 out of 10 patients without adverse effects [152].…”
Section: Analgesicsmentioning
confidence: 99%